Abyssal peridotite data from the Gakkel Ridge - Salters, Vincent (IEDA: EarthChem Library, 2017)
Abstract: Hf-Nd-Os isotopic compositions and trace elements on abyssal peridotite samples. Hf and Nd isotope and trace element are done on hand-picked clinopyroxene separates. Os isotope compositions are determined on bulk samples that are strongly leached.